2019
DOI: 10.3389/fmicb.2019.01068
|View full text |Cite
|
Sign up to set email alerts
|

Co-cultivation of Trichoderma asperellum GDFS1009 and Bacillus amyloliquefaciens 1841 Causes Differential Gene Expression and Improvement in the Wheat Growth and Biocontrol Activity

Abstract: In an effort to balance the demands of plant growth promoting and biological control agents in a single product, the technology on the co-cultivation of two microbes, Trichoderma asperellum GDFS1009 and Bacillus amyloliquefaciens 1841 has been developed and demonstrated its effectiveness in synergistic interactions and its impact on the plant growth and biocontrol potential. In this study, optimization of T. asperellum and B. amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 59 publications
3
52
0
Order By: Relevance
“…Trichoderma-Bacillus combinations are among the well-documented examples in this context. Although co-cultivation of Trichoderna and Bacillus strains on artificial growth media was frequently characterized by antagonisms (Gyu Kim et al, 2008), in many plant species, including Oryza sativa (Ali and Nadarajah, 2014), Triticum aestivum (Karuppiah et al, 2019), Cicer arietinum (Zaim et al, 2018), Solanum melongena and Capsicum annuum (Abeysinghe, 2009), synergistic beneficial effects were reported after co-inoculation. This included stimulation of germination and growth promotion, as well as biocontrol effects against fungal pathogens, such as Rhizoctonia, Fusarium and Pythium, known as important damping-off diseases in cold and wet soils with potential relevance also for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma-Bacillus combinations are among the well-documented examples in this context. Although co-cultivation of Trichoderna and Bacillus strains on artificial growth media was frequently characterized by antagonisms (Gyu Kim et al, 2008), in many plant species, including Oryza sativa (Ali and Nadarajah, 2014), Triticum aestivum (Karuppiah et al, 2019), Cicer arietinum (Zaim et al, 2018), Solanum melongena and Capsicum annuum (Abeysinghe, 2009), synergistic beneficial effects were reported after co-inoculation. This included stimulation of germination and growth promotion, as well as biocontrol effects against fungal pathogens, such as Rhizoctonia, Fusarium and Pythium, known as important damping-off diseases in cold and wet soils with potential relevance also for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbes that colonize the plant at the root can move through the plant to colonize the rest of the tissues, promoting plant health or causing different diseases. To help the plant microbiome fight against pathogens, microorganism inoculation has been used in several crops, including vineyards, in an attempt to control plant pathogens using biological agents [11,13,14]. Moreover, the possibility that plant inhabiting microorganisms could influence the flavor and productivity of grapes, impacting the organoleptic characteristics of wine, has been reported [12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wu et al 16 evaluated the antimicrobial effect of co-culturing Trichoderma asperellum GDFS1009 and Bacillus amyloliquefaciens ACCC11060 in BP broth (beef extract 0.3% and peptone 0.5%) finding the greatest effects against Botrytis cinerea by the supernatant from the co-culture than individual treatments. Other study demonstrated that in vitro co-culture of T. asperellum GDFS1009 and B. amyloliquefaciens 1841 induced the production of compounds not detected under pure cultures, attributed to the competition between them 17 . According to these findings, studies between Trichoderma spp.…”
mentioning
confidence: 98%